PENGARUH SUKU BUNGA DAN INFLASI TERHADAP RASIO PROFITABILITAS PADA BANK BUMN (Universitas Muhammadiyah Palembang, 2023)
Purpose– This research aims to provide knowledge and insight to state-owned banks about how to maximize profitability by understanding how inflation and interest rates affect profitability and to provide empirical data as reference material for further academic research.Design/methodology– The type of research used is associative research. The data used in this study is secondary data obtained from the IDX official website (www.idx.co.id). Methods of data collection using the method of documentation. The data analysis used is quantitative analysis. The analysis technique is multiple linear regression analysis with the help of the SPSS version 26 application. Findings - Based on the results of the research conducted, it was found that interest rates had a positive effect on profitability and inflation had a negative effect on profitability.